2007
DOI: 10.2134/jeq2006.0231
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Fate of the Phytotoxin Juglone in Alley Soils under Black Walnut Trees

Abstract: Juglone (5-hydroxy-1,4-napthoquinone) is a chemical released by walnut trees, which can be toxic at various levels to several plant species. A balance among competing source and sink mechanisms and rates will ultimately determine whether juglone is capable of attaining sufficient levels to be allelopathic to intercrops in a walnut tree agroforestry system. In this study, juglone's release, accumulation, and decline in soil are explored using data from soil beneath a black walnut tree (Juglans nigra L) alley cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 59 publications
(67 reference statements)
1
41
0
Order By: Relevance
“…Other compounds such as juglone or phenolic acids can accumulate in soil through a mechanism of reversible sorption (Cecchi et al 2004;von Kiparski et al 2007). The triple application of parthenin at 400 µg/g soil, however, provided no indication that parthenin accumulates in soils.…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds such as juglone or phenolic acids can accumulate in soil through a mechanism of reversible sorption (Cecchi et al 2004;von Kiparski et al 2007). The triple application of parthenin at 400 µg/g soil, however, provided no indication that parthenin accumulates in soils.…”
Section: Discussionmentioning
confidence: 99%
“…Juglone is a naturally occurring electrophile and redox-cycling compound produced by black walnut trees and other members of the Juglandacea family. It is exuded into the soil by roots or decomposing leaves and fruit, where it can be encountered by C. elegans at concentrations as high as 6.4 μmol l −1 (von Kiparski et al, 2007). Paraquat is a synthetic, contact herbicide used throughout the world in agricultural applications (Powles and Yu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As regards the occurrence and fate of phytotoxin juglone in alley soils under black walnut trees, showed that juglone accumulation in low fertility soils is plausible, and may still be worthy of consideration in management of alley agroforestry systems (Kiparski et al, 2007). Juglone is occasionally used as herbicide.…”
Section: Introductionmentioning
confidence: 99%